The Karl Marx prophet, humanist and scientist through the analysis of "The Manifesto" and its validity today - Huamaní Paliza, Frank D. (2020)
This paper analyzes the validity and transcendence of Carlos Marx's postulates through his work "The Manifesto of the Communist Party" in today's society. All this through the analysis of various fragments taken from the work of Marx and various authors of postmarxism. We will make a deconstruction of its main proposals to understand why it has become one of the most important books in history. This analysis will allow us to establish the 3 main roles Marx played in history; the humanist, scientist and prophet, for this we will analyze various cultural devices of postmarxism. The methodology we use is hermeneutic and the results allow us to establish that Carlos Marx's postulates are more valid than ever, in this context of ultraglobalization, neoliberalism and postmodernism.